PROPOSED STRATEGY IN MINIMIZING NEGATIVE REPEATED FINDINGS USING VALUE-FOCUSED THINKING AND SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) - Nurfida Hanif, Fadhila
BPOM as an institution that uses state budget has the obligation to account for it through financial reports which will then be audited by BPK. BPOM has received an Unqualified Opinion since 2014 and has successfully maintained it to this day. However, based on the 2016-2020 financial audit report by BPK, there is an increasing trend of negative repeated findings of 31.7%. The repeated findings include the management of non-tax state revenues, inventory and asset management, and others. The research begins with an analysis of the internal and external environment as well as problem analysis using fishbone and problem trees. Collecting data through analysis of BPK audit reports and interviews with financial managers, asset managers, commitment makers, internal auditors, and BPK auditors. Next, a strategy is developed to minimize repeated findings by using Value-focused thinking. Data collection techniques were carried out by interviewing commitment makers, financial managers, asset managers and internal auditors. Determination of strategic priorities using a simple multi-attribute rating technique and data collection techniques with interviews and questionnaires to the Inspector as the decision maker. The results showed that there were 20 factors causing repeated findings, which were categorized as follows: regulations, technology, people, organizations, budgets, and externals. A total of 10 alternative strategies for minimizing negative repeated findings have been identified and the results of prioritizing strategies with the SMART are as follows: (1) benchmarking, (2) policy evaluation, (3) increasing internal auditor capabilities, (4) reward punishment system, (5) implementation of PIPK, (6) IT improvement, (7) assistance, (8) FGD, (9) leadership training, and (10) employee competency improvement. The authors believe that the findings will help the leader to formulate and decide on the best strategy to minimize negative repeated findings at BPOM.